2015
DOI: 10.1074/jbc.m114.632257
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Protects against Colitis by the Maintenance of Normal Gut Microflora and Secretion of Mucus

Abstract: Background:The role of autophagy in colonic homeostasis is not clear. Results: Colonic epithelial cell-specific and autophagy-deficient mice showed exacerbation of colitis and abnormal gut microflora with less abundant antimicrobial peptide production and secretion of mucus. Conclusion: Autophagy protects against colitis by the maintenance of normal gut microflora and secretion of mucus. Significance: These findings may ultimately lead to an efficient intervention for inflammatory bowel diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 70 publications
6
74
2
4
Order By: Relevance
“…The initial activation of this process may have a beneficial role in disease, since it diminishes the risk of damage by elimination of anomalous proteins or injured organelles. It has been reported that mice lacking essential components of the autophagic machinery, such as the autophagy-related gene 7 (Atg7) were highly susceptible to colitis [36]. As regards cancer, it is not clear whether autophagy suppresses or facilitates tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…The initial activation of this process may have a beneficial role in disease, since it diminishes the risk of damage by elimination of anomalous proteins or injured organelles. It has been reported that mice lacking essential components of the autophagic machinery, such as the autophagy-related gene 7 (Atg7) were highly susceptible to colitis [36]. As regards cancer, it is not clear whether autophagy suppresses or facilitates tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms such as defects in mucus secretion (Tsuboi et al, ) or activation of the inflammmasome in myeloid cells (Lee et al, ) have been associated with an increased susceptibility to colitis in mice with a defective autophagy. However, little is known about the mechanisms that mediate amelioration of colitis through autophagy stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found upregulation of Imp1 protein levels with Atg7 deletion (Fig 6A). Prior studies suggest modest enhanced susceptibility to colitis in mice with genetic deletion of Atg7 [61]. When Atg7 DIEC and Imp1 DIEC Atg7 DIEC mice were treated with 3% DSS and compared to experiments performed in Fig 1E, we found that Imp1 WT , Imp1 DIEC , and Atg7 DIEC mice exhibited modest weight differences during recovery, whereas Imp1 DIEC Atg7 DIEC mice exhibited rapid weight loss and did not recover ( Fig 6B and C), suggesting a compensatory mechanism between Imp1 and Atg7.…”
Section: Imp1 Interacts With Autophagy Transcriptsmentioning
confidence: 99%